Effects of dietary coarsely ground corn and litter type on broiler live performance, litter characteristics, gastrointestinal tract development, apparent ileal digestibility of energy and nitrogen, and intestinal morphology. (13th February 2015) - Xu, Y.; Stark, C. R.; Ferket, P. R.; Williams, C. M.; Auttawong, S.; Brake, J.
Abstract : The objectives of this study were to evaluate the effects of the dietary inclusion of 2 coarsely ground corn (CC) levels (0 or 50%) in diets of broilers reared on 2 litter types (new wood shavings or used litter) on live performance, litter characteristics, gastrointestinal tract (GIT) development, apparent ileal digestibility (AID) of energy and nitrogen (N), and intestinal morphology. No interaction effects between CC level and litter type were observed on live performance. No litter effect was observed on live performance. Dietary inclusion of 50% CC increased BW at 35 d ( P < 0.01) and improved cumulative feed conversion ratio (FCR) at 35 and 49 d of age ( P < 0.01). The 50% CC treatment increased absolute and relative gizzard weight ( P < 0.01) and decreased jejunum unit weight (g/cm) ( P < 0.01). The new litter treatment (litter N) increased absolute and relative proventriculus weight ( P < 0.05) but did not affect gizzard weight. An interaction effect between CC level and litter type was observed for litter N, where the 50% CC treatment reduced litter N regardless of litter type ( P < 0.01), but litter N was reduced by new litter only among birds fed 0% CC ( P < 0.05). The 50% CC inclusion increased litter pH ( P < 0.05) and improved the AID of energy and N by 6.8% ( P < 0.01) and 3.5% ( P < 0.05), respectively. The 50% CC treatment increased jejunum villi tip width ( P < 0.05) and villi surface area ( P < 0.01), and decreased the muscularis layer thickness ( P < 0.01), whereas new litter increased jejunum villi and ileum villi height ( P < 0.05), jejunum villi surface area ( P < 0.01), and the ratio of jejunum villi height to crypt depth ( P < 0.01). This study showed that birds fed pelleted and screened diets containing 50% CC exhibited improved BW, FCR, and AID of energy and N, in conjunction with altered morphology of the GIT and intestinal mucosa. Litter type affected some GIT traits and functions but did not affect live performance.